IMPLEMENTATION OF THE SETTLEMENT OF MSME BAD LOANS BASED ON POJK NUMBER 11 OF 2020 DUE TO THE COVID-19 PANDEMIC (STUDY AT PT. BANK RAKYAT INDONESIA (PERSERO) TBK SURAKARTA) - Raihan Ade Izdihar; Moch. Najib Imanullah (Fakultas Hukum Universitas Sebelas Maret, 2024)
This article aims to review legal issues regarding the implementation of the settlement of MSME bad loans based on Financial Services Authority (POJK) Regulation Number 11 of 2020 at PT. Bank Rakyat Indonesia and constraints in the implementation of bad credit settlement due to Covid-19 and alternative solutions. To achieve this goal, then empirical legal research is conducted which is descriptive The data type in this study consists of primary data obtained directly from the field and secondary data obtained from the results of literature study. The primary data collection technique used is to use interview techniques, while secondary data collection techniques use downloading and collecting necessary legal materials. The data analysis techniques used are interactive analysis models. The results of this research and study, show that the implementation of economic recovery policy issued by the government has been applied well by Bank BRI, especially for Micro, Small, and Medium Enterprises (MSMEs) debtors. The form of restructuring conducted by Bank BRI Surakarta is by lowering interest rates and extending the installment period. Government policy by issuing a credit relaxation policy is a very appropriate step, especially for debtors of Micro, Small, and Medium Enterprises or MSMEs of Bank BRI Surakarta. The settlement of bad loans due to the Covid-19 pandemic at Bank BRI Surakarta has been implemented based on The Financial Services Authority (POJK) Regulation Number 11 of 2020 on The Stimulus Impact of Covid-19. An alternative solution to the constraints of the implementation of bad credit settlement due to Covid-19 is the launch of the Economic Recovery Program (PEN) through the Regulation of the Financial Services Authority (POJK) Number 11 of 2020 on Stimulus Impact of Covid-19. State-owned banks, in this case Bank BRI Surakarta has helped MSME debtors affected by Covid-19